Bivalirudin Use and One‐Month Outcome in the Context of Contemporary Antiplatelet Treatment: Insights from the Greek Antiplatelet Registry. Issue 3 (June 2014) - Alexopoulos, Dimitrios; Xanthopoulou, Ioanna; Deftereos, Spyridon; Sitafidis, George; Kanakakis, Ioannis; Hamilos, Michalis; Karayannis, George; Angelidis, Christos; Stavrou, Katerina; Vavuranakis, Manolis; Goudevenos, John A.; Stefanadis, Christodoulos; et al.
Summary Aims Little is known about the use of bivalirudin in "real life". In the context of contemporary antiplatelet treatment, we aimed to assess bivalirudin treatment patterns and short‐term (one‐month) outcome. Methods Greek Antiplatelet Registry (GRAPE) is a prospective, observational, multicenter cohort study of consecutive, moderate‐to‐high‐risk acute coronary syndrome patients undergoing percutaneous coronary intervention (PCI). We assessed bivalirudin treatment patterns and predictive factors for its use. Combined in‐hospital and one‐month major adverse cardiovascular events (MACE, including death, myocardial infarction, urgent revascularization, and stroke), and bleeding events according to Bleeding Academic Research Consortium (BARC) criteria were analyzed after propensity matching. Results Of 2047 registered patients, 480 (23.4%) were treated with bivalirudin. Multivariate analysis (C statistic 0.77, 0.75–0.80 95% CIs, P < 0.001) revealed as factors favoring bivalirudin use primary PCI, radial arterial access, presentation with positive biomarkers and use of novel P2Y12 inhibitor, whereas IIb/IIIa inhibitor administration did not. Regional trends also affected bivalirudin's choice. In 370 propensity‐matched pairs of patients who received or not bivalirudin, MACE, BARC type 1, 2 and 3 did not differ between groups: 4.1%, 21.9%, 3.2%, 3.5% and 5.1%, 18.9%, 2.7%, 4.3%, respectively, P = nonsignificant for all. Conclusions In a "real life", contemporary antiplatelet treatment registry, clinical, laboratory and logistic factors affect bivalirudin's choice, while there are no differences in one‐month outcome between bivalirudin‐treated and non‐bivalirudin‐treated patients.